Pengembangan Media Pembelajaran Matematika Berbasis Roda Pintar (ROPI) pada Materi Pecahan - Fathanah, Cindy Julya; Satinem, Yohana; Hamdan, Hamdan (Jurnal Pendidikan Matematika : Judika Education, 2023)
This research aims to produce smart wheel-based mathematics learning media for class IV students at SD Negeri 5 Lubuklinggau that is valid, practical and effective. This research is development research using the ADDIE model. This model consists of five stages, namely: analysis stage, design stage, development stage and implementation, evaluation. Data collection was carried out using observation, interviews and questionnaires. The results of the research showed that valid smart wheel-based mathematics learning media was obtained with results for language experts of 0.86, material of 0.92, and media of 0.87 in the High category. The practicality result of the teacher response test was 86.67%, the individual test was 88.96% and the small group test was 81.48% with the practicality recapitulation result being 84.08% categorized as Very Practical. The effectiveness results obtained from the pretest and posttest with a recapitulation of 0.72 are categorized as High. Conclusion, based on the results of the assessment of the validity, practicality and effectiveness of the smart wheel-based mathematics learning media (ROPI) in class IV fraction material, it is included in the valid, practical and effective category in the learning process. Keywords: Mathematics, Fraction Material, Smart Wheel (ROPI)